Skilled performance on software as a function of domain expertise and program organization. - Barfield, Woodrow (Perceptual & Motor Skills)
As part of a study on the recall of skilled and novice programmers, 23 subjects each viewed a 25-line BASIC program organized in one of three ways, executable order, random chunks, and random lines. Subjects performed a perceptual task in which they recopied a 25-line BASIC program on an answer sheet while the program remained in plain view and a memory task in which they recalled the BASIC program after a 4-min. exposure to it. For the perceptual task, the number of glances and amount of time per glance between the answer sheet and stimulus material were used as indices of recall. For the memory task, the number of lines recalled as a function of program organization and level of programming skill measured performance. Analysis indicated that skilled programmers encoded more lines of a program per glance and also spent less time examining each line of code than novices when the program was presented in executable order or random chunks. Further, skilled programmers recalled more lines of code than novices when the program was presented in executable order or random chunks but not in random lines. Implications of the results for the design of human-computer interfaces is discussed. Reprinted by permission of the publisher, 1997.